One gospel, many cultures : doing theology in context - Lawrence, Arren Bennet (Fortress Press, 2022)
"Culture is defined as the shared values and practices found in a community. When the gospel meets culture, tensions occur, especially in the application of the gospel message in a specific culture. From the Canaanite culture to the Greco-Roman and Jewish cultures, Scripture exhibits many cultures. Should Christians from a specific worldview follow all the cultural practices of the Bible? Can the believers from Kerala or Bihar in India hold on to their own indigenous cultures? How might one appropriate the message of the gospel in one's own culture? These are some of the questions addressed in this book" -- Back cover.